Technology assessment of green hydrogen in South Africa - Bwanya, Rick (Graduate School of Business (GSB), 2025)
This study investigated the sustainability indicators for green hydrogen in South Africa's Northern Cape Province to inform investment and policy decisions. Using an exploratory sequential mixed-method approach, the study first conducted a systematic literature review to identify relevant sustainability indicators. This was followed by a stakeholder survey of 16 individuals representing 11 stakeholder groups to validate and rank these indicators in the context of the Northern Cape. The stakeholders' responses on the relative importance of each of the identified sustainability indicators were registered using a 5-point Likert scale, and a weighted mean score was computed to rank each indicator. This study identified 28 sustainability indicators across environmental, economic, and social dimensions. Environmental indicators were ranked highest in importance, with water use, biodiversity impact, and human toxicity potential as the top concerns. Social indicators were ranked second, with employment and skills development emerging as critical factors. Economic indicators were ranked third, with energy efficiency, local procurement, energy supply security, and economic development as the primary considerations. The study also revealed differences in priorities between public and private sector stakeholders, with the former placing more importance on social indicators and the latter on environmental indicators, thus highlighting the need for a balanced energy technology sustainability assessment approach. Based on the findings, this study recommended a comprehensive energy technology sustainability assessment for green hydrogen be conducted that considers the diverging stakeholder views of and incorporates the key sustainability indicators established in this study. The assessment may provide results relevant to policymakers and investors alike in decision-making, thus ensuring that capital is mobilised and aligned with sustainable energy technologies, such as green hydrogen. This study contributed to the broader fields of energy technology assessment and sustainable investment and provided sustainability indicators that researchers, policymakers and investors can consider in South Africa's emerging green hydrogen economy, with a specific focus on the Northern Cape. These findings can inform sustainable development strategies and guide future research in this field.